The causal relationship between sleep and risk of psychiatric disorders: A two-sample mendelian randomization study - Chen, Pei; Qin, Jiuhang; Wang, Yueying; Yuan, Jinjin; Pan, Yang; Zhu, Bingqian (Frontiers in Genetics, 2024)
Sleep is associated with psychiatric disorders. However, their causality remains unknown.The study explored the causal relationship between seven sleep parameters (sleep duration, insomnia, sleep apnea, chronotype, daytime dozing, napping during the day, and snoring) and three psychiatric disorders including major depressive disorder (MDD), schizophrenia, and attentiondeficit/hyperactivity disorder (ADHD) using two-sample mendelian randomization (MR). Genomewide association study (GWAS) summary data for sleep parameters were obtained from the UK biobank, FinnGen biobank, and EBI databases. MR-Egger, weighted median, inverse-variance weighted (IVW), simple mode, weighted mode, maximum likelihood, penalized weighted median, and IVW(fixed effects) were used to perform the MR analysis. The heterogeneity was detected by Cochran's Q statistic. The horizontal pleiotropy was detected by MR Egger. The sensitivity was investigated by the leave-one-out analysis.Insomnia (OR=2.02, 95%CI=1.34-3.03, p=0.001, False-discovery rate(FDR) corrected p-value=0.011) and napping during the day (OR=1.81, 95%CI=1.34-2.44, FDR corrected p-value<0.001) were associated with an increased risk of MDD. Longer sleep duration(OR=2.20, 95%CI=1.24-3.90, FDR corrected p-value=0.049) had an association with the increased risk of schizophrenia, while daytime dozing (OR=4.44, 95%CI=1.20-16.41, corrected p-value=0.088)and napping during the day (OR=2.11, 95%CI=1.11-4.02, FDR corrected p-value=0.088) had a suggestive association with an increased risk of schizophrenia. Longer sleep duration had a suggestive association with a decreased risk of ADHD (OR=0.66, 95%CI=0.42-0.93, FDR corrected p-value=0.088).This study provides further evidence for a complex relationship between sleep and psychiatric disorders. Our findings highlight the potential benefits of addressing sleep problems in the prevention of psychiatric disorders.